The Influence of Impedance and Enhancement Factors of Discharge Planning Implementation at Hospital: A Systematic Review - Hari Soebagiyo; Nursalam Nursalam; Ahsan Ahsan (Jurnal Ners, 2020)
Introduction: Discharge Planning is one of various nursing duty agendas, starting from when patients are admitted to hospital up to being allowed to go home.  The phenomenon of implementation discharge planning for patients today is not optimal whereby nurses just do limited implementation of routine activities in the form of information on re-control. Based on those facts, the author wishes to study the analysis of impedance and enhancement factors in discharge planning implementation at hospitals.Methods: The researcher conducted investigation in February 2020 and involved exploration of some scientific papers journal from ScienceDirect, ProQuest, Scopus, and, PubMed as references with keywords nursing discharge planning, enhancement and impedance factors, implementation, and, hospital. This paper identified15 relevant research articles from 500 original full texts between 2010 and 2018 and analyzed inclusion criterion of enhancement and impedance factors in discharge planning implementation. It involves three RCTs, eight descriptive, and four qualitative research papersResults: As a result, there are found eight enhancement and five impedance factors influencing in discharge planning implementation. Meanwhile, from 3250 research respondents, 2125 persons reports enhanced factors contrary 1.125 samples imply impedance factors.Conclusion: The implementation discharge planning is influenced by some factors that should be given attention by nurses to do discharge planning properly.